Perubahan Makna Kosakata Bahasa Arab yang Diserap ke dalam Bahasa Indonesia - Ukhrawiyah, Faizetul (Universitas Negeri Jakarta, 2019)
The amount of Arabic vocabulary absorbed into Indonesian can cause several problems, one of which is in the field of word meaning. Absorption words that come from different languages ​​are very possible to experience changes from the original meaning. Therefore, the researcher wants to study further about the form of Arabic vocabulary that has been absorbed into Indonesian and experienced changes in meaning and what factors can cause changes in meaning in Arabic vocabulary that are absorbed into Indonesian. The method used is a descriptive qualitative method followed by analyzing the data obtained and presenting it in the form of a description. The results of this study indicate that changes in meaning that occur in Arabic vocabulary that are absorbed into Indonesian include three things, namely the expansion of meaning, narrowing of meaning, and change in total meaning. The factors that cause changes in meaning are developments in science and technology, social and cultural development, differences in usage fields, the existence of associations, differences in responses, grammatical processes, and the development of terms.